What are the Risk Factors for Antisocial Behaviour Among Low-income Youth in Cape Town? - Gardner, F.; Waller, R.; Maughan, B.; Cluver, L.; Boyes, Mark (Wiley-Blackwell Publishing Ltd., 2015)
Research in high-income countries has identified an array of risk factors for youth antisocial behavior. However, in low- and middle-income countries, despite higher prevalence of offending and antisocial behavior, there is a paucity of prospective, longitudinal evidence examining predictors. South Africa is a middle-income country with high rates of violence and crime, and a unique social context, characterized by striking income and gender inequality, and increasing number of children orphaned by AIDS. We tested predictors of antisocial behavior at community, family, and individual levels over four years. One thousand and twenty five adolescents from poor, urban South African settlements were assessed in 2005 (50 percent female; M = 13.4 years) and followed up in 2009. The sample analyzed consisted of the 723 youth (71 percent) assessed at both time points. We employed sociodemographic questionnaires and standardized scales. Validity of our antisocial behavior measure was supported by cross-sectional associations with well-evidenced concomitants of youth antisocial behavior, including drug taking and truancy. Regression analysis indicated that male gender and experience of community violence, but not poverty or abuse, predicted antisocial behavior. Despite many South African youth experiencing abuse and poverty at the family level, our findings suggest that high levels of violence in communities may be a more important factor contributing to the development of antisocial behavior, particularly among males.